Revolutionizing Children's English Vocabulary Acquisition: The Power of Games “My Talking Tom” - Supriatna, Nana; Muhria, Lanlan; Rofi’i , Agus (Journal Corner of Education, Linguistics, and Literature, 2024)
This study examines how interactive digital games, particularly "My Talking Tom," can transform how children acquire English vocabulary. By focusing on this popular virtual pet game, the research assesses its effectiveness in combining entertainment with educational benefits. Using a descriptive qualitative case study approach grounded in Skinner's theory, data were collected through direct observation. , the study investigates how the game's features—such as its dialogue, character interactions, and context-based language—aid in vocabulary learning. The results indicate that "My Talking Tom" captivates children and enhances their vocabulary skills through engaging and practical language exposure. The study highlights the potential for digital games as innovative educational tools, suggesting a shift in traditional language learning methods through technology.